An Analysis of Palliative Care Development in Africa: A Ranking based on Region-Specific Macro-Indicators - Rhee, John Y.; Garralda, Eduardo; Namisango, Eve; Luyirika, Emmanuel; Centeno, Carlos (Journal of pain and symptom management, 2018)
To date, there is no study comparing palliative care (PC) development among African countries.To analyze comparatively PC development in African countries based on region-specific indicators.Data were obtained from the African PC Association Atlas of PC in Africa, and a comparative analysis was conducted. Nineteen indicators were developed and defined through qualitative interviews with African PC experts and a two-round modified Delphi consensus process with international experts on global PC indicators. Indicators were grouped by the World Health Organization public health strategy for PC dimensions. These indicators were then sent as a survey to key informants in 52 of 54 African countries. Through an expert weighting process and ratings from the modified Delphi, weights were assigned to each indicator. Surveys were received from 89% (48 of 54) of African countries. The top three countries in overall PC development were, in order, Uganda, South Africa, and Kenya. Variability existed by dimension. The top three countries in specialized services were Uganda, South Africa, and Nigeria; in policies, it was Botswana followed by parity among Ethiopia, Rwanda, and Swaziland; in medicines, it was Swaziland, South Africa, then Malawi; and in education, it was equivalent between Uganda and Kenya, then Ghana and Zambia.Uganda, South Africa, and Kenya are the highest performing countries and were the only ones with composite scores greater than 0.5 (50%). However, not one country universally supersedes all others across all four PC dimensions. The breakdown of rankings by dimension highlights where even high-performing African countries can focus their efforts to further PC development.
Keywords: palliative care development, Africa, atlas, public health, ranking